Czy to był rok karnawału? Świadectwo odmiennych strategii wpływu w "Solidarności" - Sauerland, Karol (Er(r)go. Teoria - Literatura - Kultura, 2013)
The article employs interpretative textual analysis and contemporary literary hermeneutics. The study focuses on the relationship between individual experience and literary representation. Sauerland’s text is concerned with the difference in the aspirations and dreams of influence in “Solidarity” on the subjective transformations of the country. The text is a testimony and a clear demonstration of a dramatic collision of the network and the self-government strategy which was taken into consideration at some point and the range of the social mobilization of „Solidarity” in Poland, as well as the need to create a new model of the state, as related to the drama of the model which eventually dominated the Polish transformation, with particular attention paid to the role and influence of Lech Wałęsa. The author considers the phenomenon of “Solidarity” as a process and a real change-oriented action heading towards self-government. He uses his own observations, experiences and notes from participation in these processes, for example in the context of planning reforms of higher education. He asks a crucial question concerning “Solidarity”: was it a carnival or a revolution? If it was a revolution, was it more like the French, the Russian, or the American one? He emphasizes that only Hanna Arendt understood not only the historical, but also the “futuristic” sense of the American revolution. Leadership is different in carnival and in revolution, with completely different contexts of action, and the American version is even more significant. The author analyzes the tragic position of Lech Wałęsa, suggesting the existence of a lost alternative for the scenario of influence which was eventually accepted under the influence of Wałęsa and his supporters, even though their domination weakened the final effects of the initialized actions and processes.